2014
DOI: 10.1155/2014/495702
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of a Fetus with Ring Chromosomal 15 by Two- and Three-Dimensional Ultrasonography

Abstract: We report on a prenatal diagnosis of ring chromosome 15 in a fetus with left congenital diaphragmatic hernia (CDH) and severe intrauterine growth restriction (IUGR). A 31-year-old woman, gravida 2 para 1, was referred because of increased nuchal translucency at gestational age of 13 weeks. Comprehensive fetal ultrasound examination was performed at 19 weeks revealing an early onset IUGR, left CDH with liver herniation, and hypoplastic nasal bone. Three-dimensional ultrasound (rendering mode) showed low set ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In the ring chromosome 15 in this present study, the fetus had CDH and intrauterine growth retardation. Britto et al [2014] and Hatem et al [2007] each reported a case of prenatal diagnosis of CDH and intrauterine growth retardation in a fetus with ring chromosome 15 similar to our study. Klaassens et al [2007] reported 2 patients with a deletion of 15q26 and the phenotype consists of intrauterine growth retardation, left-sided CDH, cardiac anomalies, and characteristic facial features, similar to those seen in Fryns syndrome.…”
Section: Discussionsupporting
confidence: 88%
“…In the ring chromosome 15 in this present study, the fetus had CDH and intrauterine growth retardation. Britto et al [2014] and Hatem et al [2007] each reported a case of prenatal diagnosis of CDH and intrauterine growth retardation in a fetus with ring chromosome 15 similar to our study. Klaassens et al [2007] reported 2 patients with a deletion of 15q26 and the phenotype consists of intrauterine growth retardation, left-sided CDH, cardiac anomalies, and characteristic facial features, similar to those seen in Fryns syndrome.…”
Section: Discussionsupporting
confidence: 88%
“…Jacobsen and coworkers were the first to describe the ring chromosome 15 syndrome and since then, about 40 cases have been reported in literature. Among these, only four cases were diagnosed prenatally ( 61 ). A ring chromosome origins from a breakage in both the arms of the chromosome and a fusion of the breakpoints, with consequent loss of the distal fragments.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with those of the latest clinical reports. In addition, congenital diaphragmatic hernia (CDH) is another clinical feature described in these patients ( 7 , 61 , 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the five cases diagnosed prenatally, r (15) syndrome was founded in four fetuses with the intrauterine growth restriction (IUGR) from ultrasound exam (Glass et al, 2006; F I G U R E 2 G banding of chromosomes revealed a ring chromosome 15, karyotype (46,XX,r (15) [20]) Hatem et al, 2007;Liu, Chang, & Chen, 2001;Manolakos et al, 2009). Three-dimensional ultrasound in the rendering mode was also important in the assessment of facial deformations in fetus (low-set ears and depressed nasal bridge) (Britto et al, 2014). Due to the limited number of reported r (15) syndrome cases, and most of them were occurred before puberty, it was very difficult to assess the reproductive ability of subjects affected by ring chromosomes.…”
Section: Summary Of Clinical Characteristicsmentioning
confidence: 99%
“…Unusual mosaicism with r ( 15) and 15qs+ and a r ( 15) plus an additional small supernumerary marker chromosome 15 [sSMC( 15)] were also reported (Smith et al, 1991;Szabó et al, 2018). The ring chromosomes have been reported in multiple tissues and have been seen prenatally in both amniocytes and chorionic villous samples (Manolakos et al, 2009), as well as in post-natal blood, lymphocytes, bone marrow, and skin (Britto et al, 2014;Smith et al, 1991).…”
Section: Summary Of Molecular Characterization and Genotype-phenotype Associationmentioning
confidence: 99%